2016
DOI: 10.3390/nu8010026
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor Activation is Associated with Altered Plasma One-Carbon Metabolites and B-Vitamin Status in Rats

Abstract: Plasma concentrations of metabolites along the choline oxidation pathway have been linked to increased risk of major lifestyle diseases, and peroxisome proliferator-activated receptors (PPARs) have been suggested to be involved in the regulation of key enzymes along this pathway. In this study, we investigated the effect of PPAR activation on circulating and urinary one-carbon metabolites as well as markers of B-vitamin status. Male Wistar rats (n = 20) received for 50 weeks either a high-fat control diet or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 72 publications
(98 reference statements)
8
20
0
Order By: Relevance
“…117 Treatment of healthy individuals with fibrates (PPARA-agonists) results in increased urinary choline and betaine, 118 with similar findings in animal models. 119 Our urinary observations support our proteomic and gene level findings which together suggest that the alterations observed in NEVKP-treated kidneys may reflect increased PPARA and PPARGC1A activity.…”
Section: Discussionsupporting
confidence: 87%
“…117 Treatment of healthy individuals with fibrates (PPARA-agonists) results in increased urinary choline and betaine, 118 with similar findings in animal models. 119 Our urinary observations support our proteomic and gene level findings which together suggest that the alterations observed in NEVKP-treated kidneys may reflect increased PPARA and PPARGC1A activity.…”
Section: Discussionsupporting
confidence: 87%
“…Another limitation of this assay lies in its unreliability to reflect cellular vitamin B 12 status. Results from studies assessing serum and cellular vitamin B 12 have shown that the levels of serum B 12 do not always represent cellular B 12 status (Carmel, 2000 ; Solomon, 2005 ; Devalia et al, 2014 ; Lysne et al, 2016 ). In particular, patients with inborn errors of vitamin B 12 metabolism can present with normal or low serum values of the vitamin, while being deficient at the cellular level.…”
Section: Serum Biomarkers Of Vitamin B 12 Deficienmentioning
confidence: 99%
“…A number of studies point to the lack of correlation between serum and cellular levels of vitamin B 12 (Carmel, 2000 ; Solomon, 2005 ; Devalia et al, 2014 ; Lysne et al, 2016 ), and this is particularly important in the case of inborn errors of cobalamin metabolism whereby serum levels of the micronutrient are within the normal range(Watkins and Rosenblatt, 2013 ). In this regard, serum vitamin B 12 and holo-TC should be avoided as sole markers of B 12 deficiency in neonatal screening.…”
Section: Challenges In the Diagnosis Of Vitamin B 12 mentioning
confidence: 99%
See 1 more Smart Citation
“…An elusive aspect of vitamin B 12 metabolism concerns the lack of a distinct correlation between serum and tissue levels of the micronutrient (47)(48)(49)(50) and an unclarified role of the vascular endothelium in that homeostasis. We have previously shown that bovine aortic endothelial cells (BAECs) can take up and process Cbl to generate the 2 cofactors MeCbl and AdoCbl (27,51).…”
mentioning
confidence: 99%